Pokok-Pokok Ajaran Ahmadiyah - Santalina, Indo; Bahar, Elsa Wildia (Media Hukum Indonesia (MHI), 2024)
Ahmadiyah is a religious movement in islam founded by Mirza Ghulam Ahmad. The founder of the ahmadiyah congregation came from a respectable family , he was born on February !3 1835 , 0r 14 Shawwal 1250 H on Friday in qadian hamlet which is locted 24 km from the city of amritsar, Punjab , india. Studying the origins and movement  of the ahmadiyah movement is interesting because this movement still has followers in a number of muslim countries, including Indonesian. In this paper, using a qualitative approach, the researcher tries to trace the traces of the ahmadiyyah movement an its main ideas. This research is a literature study. The result of the research show that the emergence of the ahmadiyyah sect was motivated by social and political conditions so that various sects emerged , one of which was the sect brought by mirza ghulam ahmad on march 23 1889 in indian to eliminate the feeling of emptiness of religious outhory, as well as wanting the public to have a capable figure . direct you to the staright path.